PERENCANAAN STRATEGIS DALAM PENYELENGGARAAN RUANG TERBUKA HIJAU ( RTH ) DI KOTA SEMARANG - Hadi Dewanto; Dyah Hariani; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2013)
Strategic planning is an effort that didisplikan to make important decisions and actions that shape and guide how to be an organization, what the organization is doing and why doing anything like that. with strategic planning to identify strategies that can be used in the implementation of green open space (RTH) in Semarang City by using the eight step strategic planning process by using SWOT analysis tool, as well as the litmus test processing basic. In the implementation green open space (RTH) in Semarang City can be created properly as mandated by Act - Act No. 26 Year 2007 About Spatial Planning.